The Influence of Forced Distribution Rating System (FDRS) on Job Performance : The Mediation Role of Effort , Stress , Procedural Justice, and Distributive Justice Empirical Study on Employees at Bank Indonesia Head Office - Mohamad Ardhi Fareza; Elok Savitri Pusparini (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Job performance considered important for organizational effectiveness and can be optimized through well-designed and implemented performance appraisals to motivate employees. One of the measurement models is Forced Distribution Rating System (FDRS). The main objective of this study was to assess the effect of FDRS on job performance mediated by effort , stress , procedural justice , and distributive justice. The research data were obtained from 380 respondents through online and offline questionnaires that had undergone initial cleansing and filtering, analyzed using Covariance-Based Structural Equation Modeling (CBSEM) with the Confirmatory Factor Analysis (CFA) method using the LISREL 8.8 application . The test results showed that the Forced Distribution Rating System (FDRS) had a significant positive effect on effort (H1), procedural justice (H3), and distributive justice (H4). Effort was shown to have a significant effect on job performance (H5), while procedural justice (H7) and distributive justice (H8) also had a strong positive relationship with job performance . Effort significantly mediated the relationship between FDRS and job performance (H9), while procedural justice (H11) and distributive justice (H12) were also important mediators. In contrast, FDRS has no significant effect on stress (H2), and stress does not mediate the relationship between FDRS and job performance (H10). These findings underscore the importance of a justice-based approach in implementing an evaluation system such as FDRS to support optimal employee performance.